KECEMASAN EMOSIONAL DAN KUALITAS HUBUNGAN INTERPERSONAL: PERAN MODERASI GAYA KELEKATAN PADA GENERASI Z - Kilanta, Deyana Lovely; Budiarto, Yohanes (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Interpersonal relationship quality plays a crucial role in psychological well-being, particularly among Generation Z, who increasingly experience emotional anxiety in modern social contexts. This study aims to examine the role of emotional anxiety in the quality of interpersonal relationships in Generation Z and to investigate whether attachment style functions as a moderating variable in this relationship. The study employed a quantitative correlational design. Participants were individuals from Generation Z aged 13–28 years, recruited using convenience sampling and completing online questionnaires. The instruments used were the Quality of Relationships Inventory, the Generalized Anxiety Disorder-7, and the Adult Attachment Scale measuring close, depend, and anxiety dimensions. Data were analyzed using Jamovi with the MedMod module to test direct and moderation effects. The results showed that emotional anxiety had a significant but relatively weak effect on interpersonal relationship quality. In contrast, all three dimensions of attachment style had significant positive effects on relationship quality but did not moderate the relationship between emotional anxiety and interpersonal relationship quality. In conclusion, emotional anxiety and attachment style independently contribute to interpersonal relationship quality among Generation Z. This study contributes to the literature by clarifying the independent roles of emotional anxiety and attachment style in shaping interpersonal relationship quality, particularly within the psychosocial context of Generation Z.